2000
DOI: 10.1006/jmsc.2000.0732
|View full text |Cite
|
Sign up to set email alerts
|

Addressing ecosystem effects of fishing using marine protected areas

Abstract: This article is a synthesis of the current literature on the potential of marine protected areas (MPAs) a useful management tool for limiting the ecosystem effects of fishing, including biological and socio-economic aspects. There is sufficient evidence that fishing may negatively affect ecosystems. Modelling and case studies show that the establishment of MPAs, especially for overexploited populations, can mitigate ecosystem effects of fishing. Although quantitative ecosystem modelling techniques incorporatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
84
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(88 citation statements)
references
References 55 publications
0
84
0
4
Order By: Relevance
“…Yet, the success of protected areas depends on user compliance (Sumaila et al 2000;Moore et al 2004), and solutions that do not incorporate consumptive socioeconomic interests (scenario 1) are likely to fail because of lack of community support. We demonstrated that marine protected areas can be designed efficiently to meet the goals and objectives of multiple stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the success of protected areas depends on user compliance (Sumaila et al 2000;Moore et al 2004), and solutions that do not incorporate consumptive socioeconomic interests (scenario 1) are likely to fail because of lack of community support. We demonstrated that marine protected areas can be designed efficiently to meet the goals and objectives of multiple stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…Como resultado, las características biológicas y ecológicas de cada especie, así como las peculiaridades de cada RM (tamaño, nivel de esfuerzo pesquero, tipo de artes empleadas, etc.) parecen jugar un papel importante en la respuesta de cada especie a las medidas de protección en cada una de las dos RM analizadas, tal y como numerosos trabajos han considerado (Roberts y Polunin 1991Sluka et al 1997;Roberts 1998;Chiappone et al 2000;Sumaila et al 2000;Halpern y Warner 2002;Friedlander et al 2003;Halpern 2003;Willis et al 2003;García-Charton et al 2004;Russ et al 2005).…”
Section: Discussionunclassified
“…In this context, it is important to recall that it is well known that one of the issues in resource allocation is reconciling conflicting interests between the different entities interested in conservation and exploitation (Sumaila et al 2000). For these reasons it is very important to strike a balance when designing MPAs between the socio-economic needs and the ecological conservation needs.…”
Section: Some General Comments On Mcs In Mpasmentioning
confidence: 99%